Rare primitive deuterostomes from the Cambrian (Series 3) of Utah. (23rd November 2015) - Conway Morris, Simon; Halgedahl, Susan L.; Selden, Paul; Jarrard, Richard D.
Abstract: The fossil record of early deuterostome history largely depends on soft-bodied material that is generally rare and often of controversial status. Banffiids and vetulicystids exemplify these problems. From the Cambrian (Series 3) of Utah, we describe specimens of Banffia episoma n. sp. (from the Spence Shale) and Thylacocercus ignota n. gen. n. sp. (from the Wheeler Formation). The new species of Banffia Walcott, 1911 shows significant differences to the type species ( B . constricta Walcott, 1911 ) from the Cambrian (Series 3, Stage 5) Burgess Shale, notably in possessing a prominent posterior unit but diminished anterior section. Not only does this point to a greater diversity of form among the banffiids, but also B . episoma indicates that the diagnostic median constriction and crossover of either side of the body are unlikely to be the result of taphonomic twisting but are original features. Comparisons extend also to the Cambrian (Series 2) Heteromorphus Luo and Hu in Luo et al., 1999 and, collectively, these observations support an assignment of the banffiids to the vetulicolians. The new taxon T . ignota represents the first discovery of a vetulicystid from beyond China and also significantly extends its stratigraphic range from Series 2 Cambrian into Series 3 Cambrian. Despite overall similarities in bodyplan, T . ignota differs from other vetulicystids in a number of respects, notably the possession of an anterior zone with broad tentacle-like structures. This new discovery is consistent with the vetulicystids representing stem-group ambulacrarians.